A diplomacia egípcia no dealbar do «império» (século XV a. C.) - Daniela Martins (História - Revista da Faculdade de Letras da Universidade do Porto, 2015)
If the treaty of Kadesh (XIII B. C.) is the most evident proof of the Egyptian diplomacy, it does not summarize the subject within the pharaonic history. If on XV B. C., Egypt is able to create and maintain an «empire», much due to their political strategies and their diplomatic maneuvers. We’ll do, therefore, an analysis centered in the reigns that saw the «birth» of the Egyptian «empire», it’s «golden age», beginning with Thutmose III